2012
DOI: 10.4236/ajor.2012.21007
|View full text |Cite
|
Sign up to set email alerts
|

Who Benefits from Altruism in Supply Chain Management?

Abstract: The significant effect of social preference on strategic behavior has been convinced by recent research. Along this stream of research, we study firms' altruistic incentives in supply chains since the selfish rationality can't deal with economic behaviors. We show that the performance of the supply chain in consideration of altruism is between those of scenarios under decentralization and under integration. We further shows that a manufacturer, as a leader, should find an egoistic retailer, while a retailer, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…These behavioral preferences have a wide-ranging impact on social and economic activities. Ge et al [23] analyzed the impact of altruistic preferences on decentralized and concentrated supply chain performance. Liu et al [24] Considering carbon tax regulation and consumers’ low-carbon preference, found that the manufacturer’s and the retailer’s fairness concerns decrease their product sustainability and low-carbon promotion level, together with the profits of the system and the manufacturer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These behavioral preferences have a wide-ranging impact on social and economic activities. Ge et al [23] analyzed the impact of altruistic preferences on decentralized and concentrated supply chain performance. Liu et al [24] Considering carbon tax regulation and consumers’ low-carbon preference, found that the manufacturer’s and the retailer’s fairness concerns decrease their product sustainability and low-carbon promotion level, together with the profits of the system and the manufacturer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…And Andreoni and Miller (2002) further confirmed the rationality of altruism, which can be understand sufficiently by an economic model. Nowadays, most researches concerning altruistic preferences have focused on the many fields, such as supply chain (Ge & Hu, 2012), behavioural decision-making (Nandavar et al, 2019) and the carbon market (Salas & Roe, 2012) etc. For instance, Ge and Hu (2012) interpreted firms' cooperative incentive as their altruism, and pointed out that a manufacturer with altruistic liability would benefit both the supply chain and the retailers.…”
Section: Altruistic Theorymentioning
confidence: 99%
“…Although the original motive of economic philanthropy is self-interests rather than altruism, the practical results show that this kind of non-subjective altruism has achieved a win-win situation between enterprises and recipients (Ge & Hu, 2012). Compared with the profitable projects using other schemes, the investment return of PPP projects is typically lower.…”
Section: Introductionmentioning
confidence: 96%
“…Padula et Dagnino (2007) décrivent ainsi clairement la coopétition comme une intrusion de la compétition dans le jeu coopératif, et ils en tirent la conclusion que les déterminants de cette intrusion constituent la principale thématique de recherche à explorer. En d'autres termes, la coopétition est un état méta-stable du système, d'ailleurs confirmé par l'existence d'intérêts partiellement convergents entre les joueurs, qui génère un déséquilibre au sein d'un mode relationnel de type coopératif ; un tel déséquilibre peut être constructif dès l'instant où il fait progresser le système vers plus de performance globale et/ou individuelle (chacun des joueurs), voire favorise le déve-loppement de comportements altruistes, notamment au sein des chaînes logistiques (Ge et Hu, 2012).…”
Section: Le Pilotage Aux Interfaces : Une Perspective Coopétitiveunclassified